Unifying protocols for conducting systematic scoping reviews with application to immersive learning research - Morgado, Leonel (2020)
The progress of immersive learning research as a field requires a clear vision of its status, of the current knowledge being produced and of the open problems and gaps. Typical survey efforts however suffer from lack of systematization, providing a scattered perspective of the field. We have combined the literature on conducting systematic scoping reviews and applied it to the field, presenting the resulting protocol. It contributes a clarification on the sequence of steps and processes for delineating a gap, finding the evidence and depart from it to conduct literature reviews.